2018
DOI: 10.1039/c7ta10159g
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of vanadium sesquioxide (V2O3) nanosheets and their room-temperature sensing performance

Abstract: Single-step growth of V2O3 nanosheets on glass substrates has been established for room-temperature ammonia sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…XPS analysis showed peaks related to V–O, V–C–O, V–C–(OH) x , and H 2 O components. These components can be related to the oxygen and hydroxyl functional groups, interlayer water, and possible vanadium oxide (VO x ) species present as the result of partial surface oxidation of V 2 CT x MXene. ,,, It is previously reported that some MXenes, in particular, delaminated V 2 CT x , can be partially oxidized at their surface in ambient atmospheres or slightly elevated temperatures and form oxide and oxycarbide surface layers. ,, These results are also consistent with our recent report on thermal stability of V 2 CT x MXene under different atmospheres . The F 1s region of the XPS spectrum (Figure d) showed F components related to fluorine termination of MXenes as well as residual carbon–fluoride bonds at 684.07 and 686 eV, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…XPS analysis showed peaks related to V–O, V–C–O, V–C–(OH) x , and H 2 O components. These components can be related to the oxygen and hydroxyl functional groups, interlayer water, and possible vanadium oxide (VO x ) species present as the result of partial surface oxidation of V 2 CT x MXene. ,,, It is previously reported that some MXenes, in particular, delaminated V 2 CT x , can be partially oxidized at their surface in ambient atmospheres or slightly elevated temperatures and form oxide and oxycarbide surface layers. ,, These results are also consistent with our recent report on thermal stability of V 2 CT x MXene under different atmospheres . The F 1s region of the XPS spectrum (Figure d) showed F components related to fluorine termination of MXenes as well as residual carbon–fluoride bonds at 684.07 and 686 eV, respectively.…”
Section: Resultssupporting
confidence: 89%
“…These components can be related to the oxygen and hydroxyl functional groups, interlayer water, and possible vanadium oxide (VO x ) species present as the result of partial surface oxidation of V 2 CT x MXene. 40,44,46,47 It is previously reported that some MXenes, in particular, delaminated V 2 CT x , can be partially oxidized at their surface in ambient atmospheres or slightly elevated temperatures and form oxide and oxycarbide surface layers. 23,40,44 These results are also consistent with our recent report on thermal stability of V 2 CT x MXene under different atmospheres.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 A number of studies based on metal oxide semiconductor nanoparticles, like zinc oxide (ZnO), tin oxide (SnO 2 ), indium oxide (In 2 O 3 ), tungsten oxide (WO 3 ), molybdenum oxide (MoO 3 ) and vanadium oxide (V 2 O 5 ) were conducted towards the development of NH 3 gas sensors. [7][8][9][10] Among these metal oxides, WO 3 , an n-type semiconductor, is considered as a forefront material for chemiresistive gas sensing application. The sensing effects of WO 3 nanoparticles are determined by the capability of tungsten ions to change their valence state upon oxidation/ reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The roughness value for pure ZnO increases from 26 to 46 nm due to the influence of yttrium doping. This increase in roughness results in more active centres for gas adsorption favouring better sensing as explained by Wenzel's effect [37,38]. EDX was used to identify the presence of elements in the prepared films.…”
Section: Surface Morphological Studymentioning
confidence: 99%